Thematisation in Polish current affairs TV programmes during the 2014 European election campaign: autopoiesis in the Polish media system - Gackowski, Tomasz (Information & Media, 2016)
The aim of this study was to examine the quality of Polish public debates on the European elections; in other words, how current affairs TV programmes tried to explain the complexity of issues concerning the European Union and the essence of how the European Parliament operates to the average viewer-voter. In the study, the methodology of qualitative and quantitative content analysis were implemented. The paper focuses on the phenomenon of thematisation in the TV programmes covered in the study. Much attention in the discussions of the journalistic topics was given to such issues as the process and dynamics of a given campaign, the manner of its coverage by the media and the polls. In this regard, the results of the study confirmed a strong autopoietic (definition of the Luhmann’s theory) and self-referential nature of the electoral discourse.